2022
DOI: 10.3390/life12101504
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Role of Subcutaneous Adipose Tissue in the Pathogenesis of Obstructive Sleep Apnoea

Abstract: Introduction: Our aim was to investigate the applicability of artificial intelligence in predicting obstructive sleep apnoea (OSA) and upper airway obstruction using ultrasound (US) measurements of subcutaneous adipose tissues (SAT) in the regions of the neck, chest and abdomen. Methods: One hundred patients were divided into mild (32), moderately severe-severe (32) OSA and non-OSA (36), according to the results of the polysomnography. These patients were examined using anthropometric measurements and US of SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“… Some other studies have focused on the ability to use ultrasound or MRI imaging of the tongue for OSA prediction [ 32 , 34 ]. One research [ 34 ] showed the ability of OSA prediction using AI applied to ultrasound imaging of the UA and subcutaneous adipose tissues (SAT) in the regions of the neck, chest, and abdomen measurements [ 35 ]. The data was collected from 100 individuals, 36 without OSA and 64 with different OSA severity (32 mild, 32 moderately severe) based on their overnight PSG scores, while the DISE was used to determine the obstruction location and configuration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Some other studies have focused on the ability to use ultrasound or MRI imaging of the tongue for OSA prediction [ 32 , 34 ]. One research [ 34 ] showed the ability of OSA prediction using AI applied to ultrasound imaging of the UA and subcutaneous adipose tissues (SAT) in the regions of the neck, chest, and abdomen measurements [ 35 ]. The data was collected from 100 individuals, 36 without OSA and 64 with different OSA severity (32 mild, 32 moderately severe) based on their overnight PSG scores, while the DISE was used to determine the obstruction location and configuration.…”
Section: Methodsmentioning
confidence: 99%
“…MRI for detecting OSA results in 90% and LPW-based obstruction in 84% [ 33 ] Endoscopy 43 subjects with AHI ≥ 15 The collapsibility was significant only at the hypopharyngeal level (41.8% during wakefulness and 88.3% in DISE). 18.6% and 4.6% of patients showed laryngeal obstruction during awake and DISE examinations, respectively [ 35 ] Ultrasound 36 with AHI < 5, 32 with 5 ≤ AHI < 15 and 32 with AHI ≥ 15 OSA prediction using the ultrasound parameters achieved a sensitivity of 100% and a specificity of 91.7% [ 34 ] Ultrasound and MRI 36 with AHI < 5 and 64 with AHI ≥ 5 Using tongue parameters and anthropometric values, an ultrasound sensitivity of 94% and a specificity of 98% were achieved while MRI has 56% sensitivity and 92% specificity …”
Section: Methodsmentioning
confidence: 99%
“…The AHI represents the total number of apnea and hypopnea events per hour of sleep as recorded during an overnight sleep study. The severity of OSA can be evaluated through the AHI, which categorizes the condition into three levels: mild (5 ≤ AHI < 15), moderate (15 ≤ AHI ˂ 30), and severe (AHI ≥ 30) [ 35 ]. Apneas are characterized by a minimum of 90% reduction in airflow for at least 10 s, while hypopneas involve a decrease in respiratory signals for at least 10 s accompanied by a minimum of 3% oxygen desaturation [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory tests offer a multifaceted advantage, providing a non-invasive, easily attainable, and economical approach to assessment, while also playing a pivotal role in diagnosing various medical conditions within routine clinical practice, with notable emphasis on screening procedures and accurate disease diagnostics. Diagnostic biomarkers, including specific molecules, genes, or other biological substances, are critical tools in modern medicine, aiding in the early detection, diagnosis, and management of diseases [ 35 ]. They offer objective, quantifiable information that assists clinicians in making informed decisions about patient care, enabling insights into underlying pathology, early disease identification, monitoring illness progression, and assessing treatment effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“… 16–18 There are also many studies that utilize cephalometry, X-ray, computed tomography (CT), magnetic resonance imaging (MRI), ultrasound, and drug-induced sleep endoscopy to measure OSA-related data, including oral and maxillofacial anatomy measurements, the upper airway, respiratory muscles, subcutaneous adipose tissue (SAT), etc., to analyze the relationship between these data and the apnea-hypopnea index (AHI) and determine the upper airway collapsing, thus exploring their diagnostic efficacy for OSA. 19–21 In addition, 3D face features were further extracted in some studies to establish classification algorithms that facilitate the utilization of information regarding linear distances and angles. 22 Nevertheless, the application of these diagnostic methods in routine clinical settings is limited due to factors such as cost, human resources, and exposure to radiation.…”
Section: Introductionmentioning
confidence: 99%